Once again about the Notion of Political Responsibility in Humanism and Terror - Cormick, Claudio (2016)
In the present work we try to return to the problem of Merleau-Ponty’s historic and political evaluation of action in the light of his accounts in Humanism and Terror and their updating in the last years by commentators such as Alexandre Hubeny, Leonardo Eiff and Jérôme Melançon. We will present some arguments against two very close related theses by Merleau-Ponty: that of the “objective” evaluation of action, which holds that the subjects behavior can be described as constituing a “betrayal” or a “crime” independently of any attribution of intentions to the agents and the thesis of the “objective” responsibility of the agent, that is, the tenet that affirms that the historic and political subjects can be “responsible” or “guilty” for an outcome of their actions, that they cannot have foreseen or can be the exact opposite for what they intended.